2015
DOI: 10.1111/tid.12464
|View full text |Cite
|
Sign up to set email alerts
|

Microsphaeropsis arundinis skin and soft tissue infection in renal transplant recipients: three case reports and a review of the literature

Abstract: Microsphaeropsis arundinis, a dematiaceous mold, is emerging as a cause of skin and soft tissue infection in immunocompromised hosts. Diagnosis is challenging because of the difficulty in identifying Microsphaeropsis species morphologically and few data are available to guide optimal management. We report 3 renal transplant recipients with M. arundinis soft tissue infection, where the etiological agent was diagnosed using DNA sequencing, and who were successfully treated with prolonged courses of extended-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Furthermore, four sp 3 carbons were also found to be present; these included two methyl groups in C-4' (d C 20.3) and C-2'' (d C 21.1) with different multiplicity. 7.23) with the carbonyl group in C-1'. The hydrogens related to the methyl group H-2'' (d H 1.97) only showed correlation with C-1''; these hydrogens were represented as a simplet, indicating their position at the extremity of the ester group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, four sp 3 carbons were also found to be present; these included two methyl groups in C-4' (d C 20.3) and C-2'' (d C 21.1) with different multiplicity. 7.23) with the carbonyl group in C-1'. The hydrogens related to the methyl group H-2'' (d H 1.97) only showed correlation with C-1''; these hydrogens were represented as a simplet, indicating their position at the extremity of the ester group.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, this fungus is associated with rare infections of the skin and tissues of immunocompromised hosts. 7 Studies in the literature have reported the presence of sesquiterpenes (endowed with antifungal activity), 8 preussomerins (endowed with cytotoxic potential), 9…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 5 Five of the cases have been reported in Australia, 1 , 3 2 in Japan, 5 and one in the United States. 2 All cases described have been in immunosuppressed patients including 4 renal transplant patients 1 , 2 and 4 patients receiving long-term corticosteroids, including 2 patients with chronic kidney disease, 3 1 patient with systemic lupus erythematosus and autoimmune hepatitis, and another patient with recalcitrant temporal arteritis. 3 Similarly, both the cases described in our cases series were postrenal transplant recipients on long-term immunosuppression to prevent organ rejection.…”
Section: Discussionmentioning
confidence: 99%
“…As Coelomycetes are implanted into human skin through trauma, the dorsal hands and feet are often involved. 1 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation